The Effectiveness of the Family Hope Program (PKH) Policy in Improving the Welfare of Poor Families in Bayongbong Subdistrict, Garut Regency - Aldi Bagja Pratama (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study evaluates the effectiveness of the Family Hope Program (PKH) in improving the welfare of poor families in Bayongbong District, Garut Regency. Using a qualitative approach, data were collected through interviews, observation, and documentation. The findings indicate that PKH supports access to education and health services, yet its effectiveness is influenced by the quality of assistance, beneficiary awareness, and local context. The results highlight that the success of social programs is not solely determined by aid distribution, but also by behavioral changes and the social resilience of recipient families. The study recommends strengthening the role of facilitators and adapting policies to local needs.